Do Pharmaceuticals, Pathogens, and Other Organic Waste Water Compounds Persist When Waste Water Is Used for Recharge? - Cordy, Gail E.; Duran, Norma L.; Bouwer, Herman; Rice, Robert C.; Furlong, Edward T.; Zaugg, Steven D.; Meyer, Michael T.; Barber, Larry B.; Kolpin, Dana W. (Ground water monitoring & remediation, 2004)
A proof‐of‐concept experiment was devised to determine if pharmaceuticals and other organic waste water compounds (OWCs), as well as pathogens, found in treated effluent could be transported through a 2.4 m soil column and, thus, potentially reach ground water under recharge conditions similar to those in arid or semiarid climates. Treated effluent was applied at the top of the 2.4 m long, 32.5 cm diameter soil column over 23 days. Samples of the column inflow were collected from the effluent storage tank at the beginning (Tbegin) and end (Tend) of the experiment, and a sample of the soil column drainage at the base of the column (Bend) was collected at the end of the experiment. Samples were analyzed for 131 OWCs including veterinary and human antibiotics, other prescription and nonprescription drugs, widely used household and industrial chemicals, and steroids and reproductive hormones, as well as the pathogens Salmonella and Legionella. Analytical results for the two effluent samples taken at the beginning (Tbegin) and end (Tend) of the experiment indicate that the number of OWCs detected in the column inflow decreased by 25% (eight compounds) and the total concentration of OWCs decreased by 46% while the effluent was in the storage tank during the 23‐day experiment. After percolating through the soil column, an additional 18 compounds detected in Tend (67% of OWCs) were no longer detected in the effluent (Bend) and the total concentration of OWCs decreased by more than 70%. These compounds may have been subject to transformation (biotic and abiotic), adsorption, and (or) volatilization in the storage tank and during travel through the soil column. Eight compounds—carbamazapine; sulfamethoxazole; benzophenone; 5‐methyl‐1H‐benzotriazole; N, N‐diethyltoluamide; tributylphosphate; tri(2‐chloroethyl) phosphate; and cholesterol—were detected in all three samples indicating they have the potential to reach ground water under recharge conditions similar to those in arid and semiarid climates. Results from real‐time polymerase chain reactions demonstrated the presence of Legionella in all three samples. Salmonella was detected only in Tbegin, suggesting that the bacteria died off in the effluent storage tank over the period of the experiment. This proof‐of‐concept experiment demonstrates that, under recharge conditions similar to those in arid or semiarid climates, some pharmaceuticals, pathogens, and other OWCs can persist in treated effluent after soil‐aquifer treatment.